Proceso de elaboración de salchichas de pollo con inclusión de pasta de hueso de pierna en las empresa del grupo KFC - Cruz Rosero, Mónica Rocío (2011)
This research has as main objective the preparation of sausages including chicken leg bone paste as an alternative to improve product quality and reduce production costs and in turn set the reduction of scrap bones are thrown away which contribute to increased pollution. Why in this research will be used: chicken and ground beef from quality ingredients, besides the bone paste is a byproduct of milled chicken legs. This research was conducted in two large cities and these are Guayaquil and Quito, specifically pulp leg bone of chicken produced in the Production Plant KFC, located at km 7 ½ via Guayaquil - Duale, Province of Guayas; and the chicken sausage was prepared in Embutser Production Plant, located in Tambillo-Amaguaña, Province of Pichincha. Factorial arrangement was established AxB, with six treatments and three replications, the statistical test used was Tukey at 5% probability. The factors studied were: A (Leg Bone Pasta [PP] to 10%, 13% and 16%) and B (Fat Percentage [PG] 10% and 15%). The variables analyzed were: Sensory analysis (appearance, color, smell, taste and consistency), proximate analysis (percentage of calcium, protein, fat and pH), microbiological analysis and material balance given the best treatment of the experimental responses of the analysis sensory. During the preparation of sausages including chicken leg bone paste was held respective reception and selection of raw materials, followed by individual weighing, mixing all ingredients and additives that are part of the formulation immediately was made of the meat emulsion sausage in synthetic casings 18 mm caliber, then twisted into strings of about 10 cm, was made the respective drying, blanching, cooling, packaging, labeling and storage of the product to its distribution. Once the chicken sausage respective samples were sent to perform proximal analysis (percentage of protein, fat percentage and percentage of calcium) to SEIDLA Laboratory of Quito, the determination of pH and microbiological testing laboratory Microbiology (Plant Embutser) from the city of Quito. The sensory analysis was performed with factorial sampling method randomly to a significant group of 90 judges, who are regular customers of KFC diner. belonging to the city of Guayaquil. The results obtained in this study permitted the identification of treatment No. 5 (Pasta Bone chicken leg to 16% + Fat Percentage 10%) as the best, because that had the highest acceptance by the panel of tasters in sensory evaluation and in terms of technical parameters of the NTE INEN 1338 (1996) and Venezuelan COVENIN 2593:2002 Standard is within the established ranges. International Standard quoted as currently in our country there is an exclusive standard for the preparation of sausages and poultry. Also the percentage of positively influenced bone paste in milligrams of calcium in the chicken sausages because these are within the percentages suggested in the daily diet of people of all ages. The economic analysis was conducted microbiological treatment No. 5, with an MSRP of $ 1,18 each pack of 200 g. chicken sausage, this cost was about 5 kg as a manufacturing base. Also worth mentioning that the retail price of chicken sausages in several commissaries in the country range from $ 1,20; $ 1.55 and $ 1,12 Mrs. Chicken brand, Juris and Castile respectively. In the present study adopted the following assumptions: The amount of paste chicken leg bone in a concentration below 20% will positively influence the composition and the coloration of the final product by determining the degree of acceptability of the unit produced by the consumer. The fat content incorporated into the formulation of sausages is another factor that directs the optimum formulation with good binding capacity, good brightness and delicacy of the cut.